2006
DOI: 10.1074/jbc.m603783200
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Macroautophagy Protects against Ischemia/Reperfusion Injury in Cardiac Myocytes

Abstract: Cardiac myocytes undergo programmed cell death as a result of ischemia/reperfusion (I/R). One feature of I/R injury is the increased presence of autophagosomes. However, to date it is not known whether macroautophagy functions as a protective pathway, contributes to programmed cell death, or is an irrelevant event during cardiac I/R injury. We employed simulated I/R of cardiac HL-1 cells as an in vitro model of I/R injury to the heart. To assess macroautophagy, we quantified autophagosome generation and degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
445
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 515 publications
(479 citation statements)
references
References 71 publications
28
445
2
4
Order By: Relevance
“…However, overexpression of Atg5, a component of the autophagosomal machinery downstream of Beclin1, did not affect autophagy induction, although there is a report that enfor-ced expression of Atg5 sensitized tumour cells to anticancer drug treatment both in vitro and in vivo (Yousefi et al, 2006). Consistent with our results, other laboratories also reported the lack of effect of Atg5 overexpression in the Atg5 +/+ cells (Hamacher-Brady et al, 2006;King et al, 2008). Thus, this result implies that the autophagic machinery downstream of Beclin1-dependent induction was not a rate-limiting factor.…”
Section: Discussionsupporting
confidence: 89%
“…However, overexpression of Atg5, a component of the autophagosomal machinery downstream of Beclin1, did not affect autophagy induction, although there is a report that enfor-ced expression of Atg5 sensitized tumour cells to anticancer drug treatment both in vitro and in vivo (Yousefi et al, 2006). Consistent with our results, other laboratories also reported the lack of effect of Atg5 overexpression in the Atg5 +/+ cells (Hamacher-Brady et al, 2006;King et al, 2008). Thus, this result implies that the autophagic machinery downstream of Beclin1-dependent induction was not a rate-limiting factor.…”
Section: Discussionsupporting
confidence: 89%
“…Upregulation of autophagy has also been shown to be protective in vitro. Inhibition of autophagy in HL-1 myocytes caused increased cell death in response to simulated I/R (sI/R), whereas enhancement of the autophagic response was protective [4]. Similarly, Dosenko et al reported that inhibiting autophagy in isolated cardiac myocytes during exposure to anoxia/reoxygenation caused an increase in cell death [42].…”
Section: Autophagy In Ischemia and Reperfusionmentioning
confidence: 99%
“…Macroautophagy is the most common form of autophagy in mammalian cells and will be herein referred to as autophagy. Autophagy occurs at low levels under normal conditions, but is also upregulated in response to stress such as nutrient deprivation, hypoxia, mitochondrial dysfunction, and infection [1][2][3][4]. Autophagy can promote cell survival by generating free amino acids and fatty acids required to maintain function during nutrientlimiting conditions, or by removing damaged organelles and intracellular pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, autophagy is important for the turnover of organelles at low basal levels under normal conditions. 2 In the heart, the level of autophagy is altered not only in response to stress such as ischemia/reperfusion 14,15 but also to stress triggered by cardiovascular diseases such as cardiac hypertrophy 16 and heart failure. 17,18 Heart failure is preceded by a process termed cardiac remodeling, which encompasses the aggregate of compensatory structural and functional changes in response to stress on the chamber wall.…”
Section: Introductionmentioning
confidence: 99%